Giant mitral valve vegetation - (:unkn) unknown (My University, 2014)
Biz burada klinik durumu cerrahi müdahaleye fırsat vermeden kötüleşen ve septik emboli ve çoklu organ yetmezliğine bağlı ölen 66 yaşında mitral kapakta dev vejetasyonu olan bayan hastayı sunuyoruz. Amacımız büyük vejetasyonları olan vakalarda embolik komplikasyon riskinin ve mortalite oranlarının yüksek olduğunu, çok hızlı müdahale edilmesi gerektiğini vurgulamaktır.

We present a case of giant mitral valve vegetation in a 66-year-old woman whose clinical status deteriorated rapidly without allowing time for surgery. She died due to a septic embolism and multi- organ failure. Our aim is to stress that the risk of embolic complications is high in cases of large vegetations. The mortality rates are high and these patients should be managed immediately.
Dev mitral kapak vejetasyonu
Keywords: Genel ve Dahili Tıp